KONTRIBUSI PENDIDIKAN DAN PENGALAMAN KERJA PRAKTIK TERHADAP KESIAPAN KERJA LULUSAN SMK - Dinda Arviana Puspitasari; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2024)
Vocational school graduates have one of the highest unemployment rates, which shows that vocational school graduates have not been able to meet the standards in the world of work. This study aims to determine the role of vocational schools in contributing to producing SMK graduates who are competent and have potential in the world of work. This research uses qualitative research methods based on literature review studies from various sources. The results of the study confirm that SMK graduates can become graduates who can compete and balance with the present with the experience gained in the implementation of Industrial Work Practices. The implementation of Industrial Work Practices activities is expected to have a good impact on SMK graduates to be able to adapt and be able to apply it in their workplace environment. Thus, the creation of this Industrial Work Practice training can foster a sense of mental readiness in students. It can provide a change to Human Resources in Indonesia so that they can be qualified and able to play an important role in the work industry.